STEM TEACHER STRATEGIES FOR THE LITERACY OF ENGLISH LANGUAGE LEARNERs - Irma Savitri Sadikin; Oktian Fajar Nugroho (IKIP Siliwangi, 2022)
Teachers have a responsibility to help students who are not yet fluent in English in learning the language while they are enrolled in lessons. Researchers examined at how English language learners' academic progress could be benefited by STEM knowledge. Students can learn more about technology and how to use it in their daily lives with the help of STEM instructors. In addition, students who are learning to read and write in another language should take an English language course as part of their literacy curriculum. There are many different techniques and strategies that may be used to help students enhance their understanding of the concepts of STEM subjects as well as their academic English, which will help them become more proficient in the language and more confident in their ability to utilize it. Since this activity is cantered on Isaac Newton's first, second, and third laws of motion, STEM teachers can gain from these ideas. Keywords: English Language Learners; Cultural and Linguistic Diversity; Content-Specific TeachingMethodologies; Science, Technology, Engineering, and Math (STEM) Literacy